Pengaruh Rekrutmen, Pengembangan Karir, Pengelolaan Konflik, Lingkungan Kerja, Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Roda Sakti Surya Megah Jember - Aisya Aditya Fatikasari; Haifah; Hayatul Maspupah (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine and analyze the influence of recruitment, career development, conflict management, work environment, and compensation on employee performance at PT. Roda Sakti Surya Megah Jember. In an era of intense business competition, effective Human Resources (HR) management is crucial to improving employee performance. The method used in this study is quantitative. The research sample consisted of 60 employees, using a saturated sampling technique. In this study, data were collected through observation, interviews, literature studies, and questionnaires. Data collection through questionnaires targeting 60 employee respondents. Data analysis used to process the data includes descriptive analysis, instrument testing including validity and reliability tests, classical assumption tests including data normality tests, data multicollinearity tests, and data heteroscedasticity tests, multiple linear regression analysis, coefficient of determination, and finally hypothesis testing including partial t-tests and simultaneous F-tests. The results of the study indicate that recruitment, career development, and conflict management have a significant effect on employee performance. Conversely, the work environment does not show a significant effect. Compensation is also proven to have a significant effect on employee performance. Simultaneous tests show that all independent variables have a significant effect on employee performance.